PENERAPAN TEKNIK CERITA BERANTAI UNTUK MENINGKATKAN HISTORICAL IMAGINATION SISWA DALAM PEMBELAJARAN SEJARAH (Penelitian Tindakan Kelas di Kelas XI IPS 5 SMA Negeri 13 Bandung) - Iis Husnul Hotimah; Nana Supriatna; Yeni Kurniawati (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2018)
This research is entitled “Surastri Karma Trimurti: The aim of this research is to increase student’s Historical Imagination in Learning History. This research related to application of the Serial Story technique where this activity is a series of student`s activity in learning history to increase student’s historical imagination. The student’s Historical imagination can be said was low, seen from student’s evaluation result. They wasn’t able to explore the content of the history. Some of them also can only memorize the facts that related to the content. The students wasn’t able to imagining period of history chronogically, also wasn’t able to imagining how an even could happens and how the atmosphere in the past was like when an historical even happened. The method of this research is Classroom Action Research with Elliot’s desain. This desain has several act steps such as Recconaisance, and then a plans, observe and reflect. These steps are repeated for several cycles until the learning procces is success and compatible with the aims of this research. Data collecting technique that used in this research were observe and interview and data collecting tools were interview guidelines, field note, and observation guidelines. The indicators of this research are pupils can feel themselves in the event of history by expressing their opinions about the event. Second, revealed the possibilities that will occur if the pupils become a figure or if they were in the event. Third, describe by writing, the situation or condition also the figure’s emotion, how they feel right in that event. Fourth, imagining the story using figurative language and the last is when they are telling the story, they can express their feeling by the face expression and also body gesture according to the story. Based on this research the aim of this research was reached with the increasing point in every indicator.